Bentuk dan Makna Personifikasi dalam Antologi Puisi "Rindu yang Dalam" Karya Rokim: Analisis Stilistika: Forms and Meanings of Personification in Rokim’s Poetry Anthology “Rindu yang Dalam”: A Stylistic Analysis - Rahayu, Sri; Kiromah, Annisya Fatul; Yani, Mega; Andayani, Alya Fitri Eka; Damara, Hesty; Nopitasari, Fani; Sihaloho, Futri Aliyah Br.; Stevanie, Adella Inestha (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study examines the use of personification in Rokim’s poetry anthology, “Rindu Yang Dalam”. Personification is one of the most frequently used literary devices in poetry to create imaginative expressions and enhance the emotional impact of literary works. The purpose of this study is to identify the forms and meanings of personification found in these poems. This study employs a descriptive qualitative method with a stylistic focus. The data source is Rokim’s poetry anthology, “Rindu Yang Dalam”. Data was collected using hermeneutic techniques, including reading, recording, and classifying poetic expressions that contain personification. Data analysis was conducted through identification, classification, interpretation, and drawing conclusions. The results of this study show that personification in the anthology serves to bring natural objects and abstract ideas to life by attributing human characteristics to them. The use of personification also reinforces imagery, enhances poetic beauty, and deepens the emotional meaning conveyed by the poets. This study contributes to the development of literary studies, particularly in the analysis of figurative language and poetic appreciation in the field of language and literature.